Epidemiology and Changes in Mortality of Sepsis After the Implementation of Surviving Sepsis Campaign Guidelines. (September 2019) - Herrán-Monge, Rubén; Muriel-Bombín, Arturo; García-García, Marta M.; Merino-García, Pedro A.; Martínez-Barrios, Miguel; Andaluz, David; Ballesteros, Juan Carlos; Domínguez-Berrot, Ana María; Moradillo-Gonzalez, Susana; Macías, Santiago; Álvarez-Martínez, Braulio; Fernández-Calavia, M. José; et al.
Purpose: To determine the epidemiology and outcome of severe sepsis and septic shock after 9 years of the implementation of the Surviving Sepsis Campaign (SSC) and to build a mortality prediction model. Methods: This is a prospective, multicenter, observational study performed during a 5-month period in 2011 in a network of 11 intensive care units (ICUs). We compared our findings with those obtained in the same ICUs in a study conducted in 2002. Results: The current cohort included 262 episodes of severe sepsis and/or septic shock, and the 2002 cohort included 324. The prevalence was 14% (95% confidence interval: 12.5-15.7) with no differences to 2002. The population-based incidence was 31 cases/100 000 inhabitants/year. Patients in 2011 had a significantly lower Acute Physiology and Chronic Health Evaluation II (APACHE II; 21.9 ± 6.6 vs 25.5 ± 7.07), Logistic Organ Dysfunction Score (5.6 ± 3.2 vs 6.3 ± 3.6), and Sequential Organ Failure Assessment (SOFA) scores on day 1 (8 ± 3.5 vs 9.6 ± 3.7; P < .01). The main source of infection was intraabdominal (32.5%) although microbiologic isolation was possible in 56.7% of cases. The 2011 cohort had a marked reduction in 48-hour (7% vs 14.8%), ICU (27.2% vs 48.2%), and in-hospital (36.7% vs 54.3%) mortalities. Most relevant factors associated with death were APACHE II score, age, previous immunosuppression and liver insufficiency, alcoholism, nosocomial infection, and Delta SOFA score. Conclusion: Although the incidence of sepsis/septic shock remained unchanged during a 10-year period, the implementation of the SSC guidelines resulted in a marked decrease in the overall mortality. The lower severity of patients on ICU admission and the reduced early mortality suggest an improvement in early diagnosis, better initial management, and earlier antibiotic treatment.